Denkwürdigkeiten einer reise nach dem russischen Amerika, nach Mikronesien und durch Kamtschatka - Kittlitz, F. H. (Friedrich Heinrich), Freiherr von, 1799-1874. (Gotha, J. Perthes, 1858)
Master microform held by: ResP. The author was a naturalist on Lütke's voyage round the world, 1826-1829. Howes, U.S.IANA, Eberstadt Mode of access: Internet.